Scouring protection of bridge sub-structure - Mohammed Salem, M Aboudina (2021)
The substructure element of bridge subjected to flow of water is liable to large effect of scouring development depending on the nature of the water bed , flow velocity and the geometry of the substructure. Due to the scouring effect of flowing water at bridge substructure scour hole formed. If such bridges are allowe'd to with stand the high flow rate without any form of protection, the damage to the bridge substructure will definitely be severe. According to the experimentation conducted on the physical model, the maximum scour hole diameter and the maximum scour hole depth were found to be 72 mm and 28 mm respectively. Like wise, those piers which are protected using any one of the four illustrated methods ( Collar protection , Slot protedion , Riprap protection and piles front of pier protection ) have shown some reasonable percentage reduction in the scour hole geometry . The experimental result from the present study confirmed the effectiveness and efficiency of the studied four mentioned methods to protect bridge substructure. The reduction in the diameter of the scour holes before and after protection were found as follows: - Using multiple collar with 65% reduction. - Using rip rap with 58% reduction. - Using slot at the top of pier with 34% reduction. - Using slot at middle of pier with 45% reduction. - Using slot at bottom of pier with 4% reduction. - Using collar at top of pier with 50% reduction. - Using collar at middle of pier with 43% reduction. - Using collar at bottom of pier with O % reduction. - Using pile front of pier with 16% reduction. PERPUSTAIA~N KEJURlJTEftAA, OAN ~ENIBINA UNIYERSm PUTRA MALAYSIA Comparing all the methods, the multiple collar method was found to be the most efficient one among the four tested methods. The advantage of multiple collar is to control the vortices occured at the pier circumference. In Malaysia Public Work Department (JKR) used protection method in which the piles cap is deeper than the scour depth.